Properties of Caulobacter Ribonucleic Acid Bacteriophage φCb5 - Bendis, Inakaren (J Virol, 1970)
The ribonucleic acid (RNA) bacteriophage φCb5, which specifically infects only one form of the dimorphic stalked bacterium Caulobacter crescentus, has been obtained in high yield. Since the phage is extremely salt-sensitive, a purification procedure was devised which avoided contact with solutions of high ionic strength. Phage φCb5 was studied with respect to the physical and chemical properties of both the phage and its RNA. In an electron microscope, the phage particles appear as small polyhedra, 23 nm in diameter. The phage is similar to the Escherichia coli RNA phages in that it (i) sediments at an S(20, w) of 70.6S, (ii) is composed of a single molecule of single-stranded RNA and a protein coat, (iii) contains two structural proteins, and (iv) apparently contains the genetic capacity to code for a coat protein subunit, a maturation-like protein, and an RNA polymerase. Phage φCb5 differs from the E. coli RNA phages in (i) host specificity, (ii) salt sensitivity, and (iii) the presence of histidine, but not methionine, in the coat protein. IMAGES: